REPRESENTATIONS OF OIL COMPANIES AND ENVIRONMENTAL COLLAPSE IN CHRISTIE WATSON’S TINY SUNBIRDS FAR AWAY - ONWUKA , Edwin; OMESU, Modupeoluwa (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This study explores the representation of Western oil companies and environmental degradation in Christie Watson’s Tiny Sunbirds Far Away, situating the novel within the broader discourse of environmental degradation and socio-political unrest in the Niger Delta. Through the voice of the young narrator, Blessing, Watson crafts a poignant narrative that unveils the destructive impact of oil exploitation on both the natural environment and the lived realities of local communities. The analysis foregrounds the oil company not merely as an economic actor but as a faceless embodiment of neocolonial exploitation, ecological devastation, and systemic injustice. By highlighting the loss of traditional livelihoods, the rise of militancy, and the deterioration of health and social structures, the novel underscores the deep entanglement between environmental collapse and human suffering. Drawing on eco-critical perspective, this study shows how Watson’s work, despite being authored by an outsider, amplifies silenced voices and confronts global complicity in the Niger Delta crisis. Ultimately, the research affirms literature’s power to humanize ecological destruction, transforming statistics of oil spills and gas flares into lived experiences of pain, resilience, and resistance.